A Rare Case of Mechanical Small Bowel Obstruction Secondary to Herniation of a Part of the Ileum through a Defect in the Meso-appendix with Appendicitis and its Laparoscopic Management - Gnanaselvam, Pamathy; Dishantha Pathiragoda, Gabadage Don Harsha; Wickramaratne, Saranga Eshanie; Mathivannan, G; Karunanithy, Pirahanthan (Archives of Case Reports, 2025)
Small Bowel Obstruction (SBO) resulting from internal herniation through a defect in the mesoappendix is extremely rare, with only a few documented cases found in the literature in the context of acute appendicitis. We are presenting a case of a 79-year-old female who presented with atypical abdominal pain with a history of a fall. Due to persistent abdominal pain and tenderness on examination, further investigations were conducted. A Computed Tomography (CT) scan revealed SBO with a transition point at the terminal ileum, suspected to be caused by adhesions or mesenteric twisting. Laparoscopic exploration identified a herniated loop of the bowel through a defect in the mesoappendix, alongside an inflamed appendix containing fecaliths. The obstruction was successfully relieved via a laparoscopic approach, with an appendectomy performed concurrently. The postoperative period was uncomplicated. This case underscores the importance of considering rare causes of intestinal obstruction, particularly when clinical presentation is atypical. Early diagnosis and timely surgical intervention are crucial for favorable outcomes. In cases of SBO, rare pathologies should always be considered before making surgical decisions. This case also highlights the importance of considering the length of appendix and its associated risks in mechanical obstruction.